The Effectiveness of Digital Marketing Strategies in Increasing Purchases Intention in Electric Car Among Millennials in Bandung - Noviany, Henny; Mulyana, Asep; Nidar, Sulaeman Rahman (Ilomata International Journal of Management, 2025)
The rapid development of digital technology has changed consumer behavior, especially among millennials who heavily rely on online platforms for information and transactions. In the automotive industry, the digital market has become the primary choice for exploring and purchasing vehicles, including electric cars, which are gaining more attention as awareness of environmentally friendly transportation increases. However, the adoption rate of electric vehicles among millennials in Bandung is still relatively low, necessitating more effective digital marketing strategies. This study aims to analyze the effectiveness of digital marketing strategies implemented through the automotive market in increasing the purchase intention of electric vehicles among millennials. A quantitative approach that includes descriptive and associative research. Additionally, the method used in this research is a survey method distributed to 398 millennial respondents in Bandung. The research results show that educational content, interactive engagement through marketplace features, and transaction ease have a positive and significant impact on purchase intention. This study concludes that digital marketing strategies through automotive marketplaces are effective in shaping positive perceptions and stimulating the interest of the millennial generation in electric cars. Practical implications suggest that industry players should optimize digital marketing strategies focused on consumer education and engagement to increase the market penetration of electric vehicles.